When Brand Attitudes Affect the Customer Satisfaction-Loyalty Relation: The Moderating Role of Product Involvement - Suh, Jung-Chae; Youjae, Yi (Journal of consumer psychology, 2006)
Drawing on the attitude accessibility and stability theories, we investigate the moderating role of product involvement in the customer satisfaction-loyalty relation. Structural equation modeling shows that customer satisfaction has both direct and indirect effects on loyalty, whereas ad attitudes and corporate image have only indirect effects through their mediating influence on brand attitudes. Furthermore, product involvement decreases the direct effects of satisfaction on brand attitudes and loyalty, but it increases the indirect effects of ad attitudes and corporate image.